Pengaruh Pemanfaatan Mobile Banking Dan Kualitas Pelayanan Pada Bank BRI Cabang Bengkayang Terhadap Kepuasan Nasabah - Samuel Jolin; Blasius Manggu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to determine the effect of mobile banking and services on BRI Bank customer satisfaction. The sampling technique used in this study was purposive sampling technique, which was chosen because the researcher used his own judgment in selecting members of the population who were considered to be able to provide information, and the number of samples used was 150 respondents. The research results were collected through a questionnaire which was processed and analyzed using multiple regression analysis. The data quality test in this study is the Person Correlation validity test, the reliability test uses Cronbach Alpha. For the classic assumption test using the normality test,. For the hypothesis test used in this study, namely multiple linear regression, t test and determination coefficient (R2 test). The results of this study indicate that mobile banking and service have a positive and significant effect on BRI Bank customer satisfaction.